2015
DOI: 10.1016/j.apenergy.2014.10.086
|View full text |Cite
|
Sign up to set email alerts
|

The effects of radiative heat transfer during the melting process of a high temperature phase change material confined in a spherical shell

Abstract: openAccessArticle: Falsecover date: 2015-01-15pii: S0306-2619(14)01146-5Harvest Date: 2016-01-06 13:08:31issueName:Page Range: 675-675href scidir: http://www.sciencedirect.com/science/article/pii/S0306261914011465pubType

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…The capsules began to melt after 750 seconds, and by 1000 seconds the first 3 capsules started melting. As was seen in previous work by the authors, melting in cylindrical capsules began at the PCM‐void interface along the capsule edge (Figure A,B). Note that Figure shows only if a cell within the capsule is solid or liquid.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The capsules began to melt after 750 seconds, and by 1000 seconds the first 3 capsules started melting. As was seen in previous work by the authors, melting in cylindrical capsules began at the PCM‐void interface along the capsule edge (Figure A,B). Note that Figure shows only if a cell within the capsule is solid or liquid.…”
Section: Resultssupporting
confidence: 82%
“…Using a similar approach, Archibold et al modeled a high‐temperature capsule using NaNO 3 and obtained similar results. The authors then went on to investigate the effect of radiation on the melting process of high‐temperature PCM . The effect of an internal void on the melting of various sized cylindrical EPCM capsules with an exterior convective boundary condition was investigated by Elmozughi et al Their results showed that the presence of an internal void profoundly affects the internal heat transfer.…”
Section: Introductionmentioning
confidence: 99%
“…To the author's knowledge, there are few published literatures that considered the effect of thermal radiation in PCM-based thermal energy storage. Archibold et al [28] conducted a numerical study on the thermal characteristics of a single spherical capsule in consideration of the influence of radiative heat transfer during the phase change process. The discrete ordinate method was used to solve the radiative transfer equation.…”
Section: Introductionmentioning
confidence: 99%
“…The transition from a conductive to a convective regime produced a significant increase in thermal exchange with a reduction in charging and discharging times and consequent increase in available thermal power and system efficiency. The conditions necessary to establish these convective motions have been extensively studied both experimentally [30,[34][35][36] and numerically [37][38][39][40][41]. The last goal is to promote this sort of heat exchange within the LHTES to achieve an optimized and efficient system.…”
Section: Advancements In Energy Storage Technologiesmentioning
confidence: 99%